The Meaning of Syarab in QS. An-Nahl [16]:69: Integrating Qur’anic Exegesis and Roland Barthes’ Semiotics - Muliadi, Muliadi; Febiani, Astri Vitria; Millah, Asef Syaeful (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2025)
The interpretation of the Qur’anic verses does not stop at a literal understanding, but demands an approach capable of uncovering layers of symbolic meaning. This study analyzes the term syarab in QS. An-Nahl [16]:69 using Roland Barthes’ semiotic theory, which divides meaning into two sign systems: the first level (denotation/linguistics) and the second level (myth/connotation). This research employs a qualitative method with descriptive-analytical analysis through library research. The peimary data sources include the Qur’an, books of tafsir (exegesis), and hadith, supported by secondary data from dictionaries and related articels. The results indicate that denotatively, syarab meand “a drink”, which is anything that can be consumed. At the connotative level, syarab is understood as honey, which has various colors and healing properties, as affirmed in various classical and modern exegesis books. Honey is positioned as a symbol of divine pleasure, a sign of Allah’s power, and a medium for healing since the time of the Prophet. Barthes’ semiotic approach expands the scope of interpretation of the Qur’anic text by bridging textual and contextual meanings, and proves the relevance of semiotic studies in Qur’anic exegesis. This finding contributes to the strengthening of contemporary exegesis methodology and opens opportunities for further research on the application of semiotics in Qur’anic studies. Penafsiran ayat-ayat Al-Qur’an tidak hanya berhenti pada pemahaman literal, namun menuntut pendekatan yang mampu mengungkap lapisan makna simbolik. Kajian ini menganalisis istilah syarab dalam QS. An-Nahl [16]:69 menggunakan  teori semiotika Roland Barthes yang membagi makna  ke dalam dua system tanda: tingkat pertama  (denotasi/linguistik) dan tingkat kedua (mitos/konotasi). Penelitian ini menggunakan metode kualitatif dengan analisis deskriptif-analisis melalui studi kepustakaan,. Sumber data primer meliputi Al-Qur’an, kitab-kitab tafsir, dan hadits, didukung data sekunder dari kamus dan artikel terkait. Hasil penelitian menunjukkan bahwa secara denotative syarab bermakna “minuman”, yaitu segala sesuatu yang dapat diminum. Pada tingkat konotatif, syarab dipahami sebagai madu yang memiliki beragam warna serta khasiat penyembuhan, sebagaimana ditegaskan dalam berbagai kitab tafsir klasik dan modern. Madu diposisikan sebagai symbol kenikmatan ilahi, tanda kekuasaan Allah, serta media  penyembuhan sejak masa Nabi. Pendekatan semiotika Barthes memperluas ruang interpretasi terhadap teks Al-Qur’an dengan menjembatani makna tekstual dan kontekstual, serta membuktikan relevansi kajian semiotika dalam studi tafsir Al-Qur’an. Temuan ini berkontribusi pada penguatan metodologi tafsir kontemporer dan membuka peluang penelitian lanjutan mengenai penerapan semiotika dalam studi Al-Qur’an.